2002
DOI: 10.1128/aem.68.10.4951-4955.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inactivation of Hepatitis A Virus by Chlorine

Abstract: The study was intended to investigate the feasibility of reverse transcription-PCR (RT-PCR) for evaluation of the efficacy of inactivation of viruses in water and to elucidate the mechanisms of inactivation of hepatitis A virus (HAV) by chlorine. Cell culture, enzyme-linked immunosorbent assay, and long-overlap RT-PCR were used to detect the infectivity, antigenicity, and entire genome of HAV inactivated or destroyed by chlorine. The cell culture results revealed the complete inactivation of infectivity after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 16 publications
6
72
0
Order By: Relevance
“…4), suggesting that the latex sap affected the viral capsids but not the genomes. Ag-ELISA has been used previously to show the negative effects of disinfectants on virus antigenicity (33,34). Using Ag-ELISA, we showed that the latex sap affected the antigenicity of SaV (Fig.…”
Section: Fig 4 Sapovirus Interaction With Lettuce Leaf Milky (Latex) mentioning
confidence: 99%
“…4), suggesting that the latex sap affected the viral capsids but not the genomes. Ag-ELISA has been used previously to show the negative effects of disinfectants on virus antigenicity (33,34). Using Ag-ELISA, we showed that the latex sap affected the antigenicity of SaV (Fig.…”
Section: Fig 4 Sapovirus Interaction With Lettuce Leaf Milky (Latex) mentioning
confidence: 99%
“…Two different RT-PCR approaches have been used for determining viral infectivity. One approach involves determining the presence of an intact genome or amplifiable undamaged genome by direct RT-PCR (48,51,74,75). The second uses coupling of the RT-PCR with a pre-PCR sample treatment that can determine the integrity of the viral capsid prior to extraction and purification of nucleic acid and subsequent enzymatic amplification (56,57).…”
Section: Determination Of Viral Infectivity Using Pcrmentioning
confidence: 99%
“…Monochloramine disinfection also decreased the numbers of infectious viruses, as measured by plaque assays. Chemical disinfectants such as monochloramine have been reported to damage both the viral genome (22,23,25,27) and capsid proteins (22,28,42). To assess which mechanism was more likely for monochloramine inactivation, monochloramine-disinfected virus samples were further analyzed for E1A protein synthesis and DNA replication, as a method to assess the ability of the disinfected viral capsid to enter the host cell and to deliver genetic material to the host cell nucleus and as a measure of DNA damage by monochloramine disinfection, respectively.…”
Section: Uv Inactivation Kineticsmentioning
confidence: 99%